Marital Satisfaction, Sex, Age, Marriage Duration, Religion, Number of Children, Economic Status, Education, and Collectivistic Values: Data from 33 Countries - Sorokowski, Piotr (2017)
Forms of committed relationships, including formal marriage arrangements between men and women, exist in almost every culture (Bell, 1997). Yet, similarly to many other psychological constructs (Henrich et al., 2010), marital satisfaction and its correlates have been investigated almost exclusively in Western countries (e.g., Bradbury et al., 2000). Meanwhile, marital relationships are heavily guided by culturally determined norms, customs, and expectations (for review see Berscheid, 1995; Fiske et al., 1998). While we acknowledge the differences existing both between- and within-cultures, we measured marital satisfaction and several factors that might potentially correlate with it based on self-report data from individuals across 33 countries. The purpose of this paper is to introduce the raw data available for anybody interested in further examining any relations between them and other country-level scores obtained elsewhere. Below, we review the central variables that are likely to be related to marital satisfaction.